2009
DOI: 10.1039/b820070j
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation and other phase transformations mapped in saturated phosphatidylcholine/DSPE-PEG2000 monolayers

Abstract: Mixtures containing a saturated phosphatidylcholine (PC)-lipid and polyethylene glycol (PEG)-lipid have been widely used in lipid bilayer and monolayer systems, in particular for forming drug delivery stealth liposomes and for stabilizing medical microbubble ultrasound contrast agents. The miscibility and phase behavior of these systems have been incompletely explored and controversial. Here, using complementary experimental methods and analysis, we examine the phase behavior and construct complete surface pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
104
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(118 citation statements)
references
References 30 publications
13
104
1
Order By: Relevance
“…28 The large size of polymeric domains suggests their potential to crowd membrane surfaces, producing steric pressure. Several studies have shown that membrane-conjugated polymers such as polyethylene glycol (PEG) chains can generate significant lateral steric pressure, sufficient to influence lipid phase behavior 29 and at very high densities, sufficient to induce formation of coexisting gel-gel phases owing to depletion attraction effects. 3032 Additionally, simply attaching polymers to the membrane surface comes at an entropic cost 33 such that polymers prefer curved surfaces 34 and sterically repel other molecules including other PEG chains.…”
Section: Introductionmentioning
confidence: 99%
“…28 The large size of polymeric domains suggests their potential to crowd membrane surfaces, producing steric pressure. Several studies have shown that membrane-conjugated polymers such as polyethylene glycol (PEG) chains can generate significant lateral steric pressure, sufficient to influence lipid phase behavior 29 and at very high densities, sufficient to induce formation of coexisting gel-gel phases owing to depletion attraction effects. 3032 Additionally, simply attaching polymers to the membrane surface comes at an entropic cost 33 such that polymers prefer curved surfaces 34 and sterically repel other molecules including other PEG chains.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a lipid monolayer can be subjected to more than double the surface pressure of a lipid bilayer (~30 mN/m), where these lipid-linked oligonucleotides are reported to insert essentially irreversibly 19. Lipid shelled microbubbles will shrink in size at a rate roughly inversely dependent upon the sum of the radius and the shell gas transfer resistance times water diffusivity until the monolayer surface pressure approaches ~72 mN/m, a pressure reachable by DSPC 29. This pressure corresponds to an interfacial tension of zero mN/m and zero Pa Laplace overpressure 23.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison to the time scales used for incubation here, 20 minutes and 2 hours, an estimate of the ejection time for an average sized (4 µm radius) microbubble can be made based upon a recent theoretical analysis by Sakar et al33 where dissolution of similarly coated microbubbles in air-saturated media is modeled. We assume an average surface tension during dissolution of 36 mN/m and a decrease to one-fifth surface area (area change for a similar lipopolymer to reach a 5 mN/m ejection surface tension)29. Figure 8 of Sakar et al33 gives an average dissolution rate of approximately −2.5 µm/hr, and therefore a time of approximately 1 hour for the necessary decrease in area.…”
Section: Resultsmentioning
confidence: 99%
“…The use of chitosan is based on its potential to reduce lipid relaxation (e.g. lateral diffusion) (Baumgart & Offenhausser, 2003) and therefore, maintain a stiff structure that diminishes phospholipid instabilities, such as buckling and folding mechanisms over timer (Garg et al, 2013;Lozano & Longo, 2009). …”
Section: Introductionmentioning
confidence: 99%